Pengembangan LKPD PAI dan Budi Pekerti Pada Materi Membiasakan Perilaku Terpuji Kelas II Menggunakan Teka-Teki Silang (TTS) di SD Negeri 04 Kubang Putiah - Zarury, Ibnati; I, Iswantir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was motivated by the feeling of boredom caused by students in learning, especially in learning LKPD. So, to increase students' enthusiasm and interest in learning and improve their cognitive abilities, LKPD was developed. Development Research or Research and Development is a research method used to produce certain products and test the effectiveness and practicality of these products. So this research aims to design an LKPD using Crossword Puzzles (TTS) as teaching material on the material of Getting Accustomed to Class II Praiseworthy Behavior at SD Negeri 04 Kubang Putiah which is valid, practical and effective for use in learning. Developing LKPD using Crossword Puzzles (TTS) utilizes the Canva and Puzzlemaker applications as supporting media to make the LKPD development more interesting. The research that has been carried out and the developments that have been designed are declared very valid with an average of 0.83, then the practicality test is declared very practical with an average value of 0.92 and finally the test carried out on 20 students, the product is declared very effective with an average of -average 0.80.